Genomic and Physiological Traits of the Marine Bacterium Alcaligenes aquatilis QD168 Isolated From Quintero Bay, Central Chile, Reveal a Robust Adaptive Response to Environmental Stressors - Durán, Roberto E.; Méndez, Valentina; Rodríguez-Castro, Laura; Barra-Sanhueza, Bárbara; Salvà-Serra, Francisco; Moore, Edward R. B.; Castro-Nallar, Eduardo; Seeger, Michael (Frontiers in Microbiology, 2019)
Alcaligenes aquatilis QD168 is a marine, aromatic hydrocarbon-degrading bacterium, isolated from an oil-polluted sediment of Quintero Bay, an industrial-coastal zone that has been chronically impacted by diverse pollutants. The aims of this study were to characterize the phylogenomic positions of Alcaligenes spp. and to characterize the genetic determinants and the physiological response of A. aquatilis QD168 to model environmental stressors (benzene, oxidizing agents, and salt). Phylogenomic analyses, using 35 housekeeping genes, clustered A. aquatilis QD168 with four other strains of Alcaligenes spp. (A. aquatilis BU33N, A. faecalis JQ135, A. faecalis UBA3227 and A. faecalis UBA7629). Genomic sequence analyses of A. aquatilis QD168 with 25 Alcaligenes spp., using ANIb, indicated that A. aquatilis BU33N is the closest related strain, with 96.8% ANIb similarity. Strain QD168 harbours 95 genes encoding proteins of seven central catabolic pathways, as well as sixteen peripheral catabolic pathways/reactions for aromatic compounds. A. aquatilis QD168 was able to grow on 3-hydroxybenzoate, 4-hydroxybenzoate, benzoate, benzene, 3-hydroxycinnamate, cinnamate, anthranilate, benzamide, p-aminobenzoate, nicotinate, toluene, biphenyl and tryptophan, as sole carbon or nitrogen source. Benzene degradation was further analyzed by growth, metabolite identification and gene expression analyses. Benzene strongly induced the expression of the genes encoding phenol hydroxylase (dmpP) and catechol 1,2-dioxygenase (catA). Additionally, 30 genes encoding transcriptional regulators, scavenging enzymes, oxidative damage repair systems and isozymes involved in oxidative stress response were identified. Oxidative stress response of strain QD168 to hydrogen peroxide and paraquat was characterized, demonstrating that A. aquatilis QD168 is notably more resistant to paraquat than to H2O2. Genetic determinants (47 genes) for osmoprotective responses were identified, correlating with observed high halotolerance by strain QD168. The physiological adaptation of A. aquatilis QD168 to environmental stressors such as pollutants, oxidative stress and salinity may be exploited for bioremediation of oil-polluted saline sites.